Implementasi Fuzzy Mamdani pada Seleksi Penerimaan Mahasiswa Baru - Agung Nugroho; Donny Maulana (Jurnal Pelita Teknologi, 2020)
The process of selecting new students at a tertiary institution is one of the stages of the admission process. In the process, not all applicants will be accepted, but only student candidates who fulfill the criteria will be selected. So that the selection process needs to be done based on the stages that have been determined. This research aims to make a new student admission selection system modeling using the fuzzy inference Mamdani method. Fuzzy Mamdani is used because it has characters such as the human core in processing data based on several determining criteria. Based on the results of the validation of the new student selection data, the Mamdani method can be used in the admission system